Synthesis, Separation, and Characterization of Small and Highly Fluorescent Nitrogen‐Doped Carbon NanoDots. (6th January 2016) - Arcudi, Francesca; Đorđević, Luka; Prato, Maurizio
Abstract: A facile bottom‐up approach to carbon nanodots (CNDs) is reported, using a microwave‐assisted procedure under controlled conditions. The as‐prepared nitrogen‐doped CNDs (NCNDs) show narrow size‐distribution, abundant surface traps and functional groups, resulting in tunable fluorescent emission and excellent solubility in water. Moreover, we present a general method for the separation of NCNDs by low‐pressure size‐exclusion chromatography, leading to an even narrower size distribution, different surface composition, and optical properties. They display among the smallest size and the highest FLQYs reported so far. 13 C‐enriched starting materials produced N 13 CNDs suitable for thorough NMR studies, which gave useful information on their molecular structure. Moreover, they can be easily functionalized and can be used as water‐soluble carriers. This work provides an avenue to size‐ and surface‐controllable and structurally defined NCNDs for applications in areas such as optoelectronics, biomedicine, and bioimaging.